Ocena wsparcia rozwoju zasobów ludzkich ze środków funduszy strukturalnych w Polsce - Mroczek, Arkadiusz (Evaluation of Human Resources Development Support from Structural Funds in Poland, 2006)
Current outlooks on regional competitiveness emphasize the role of human resources, connecting it with building a knowledge based economy. Due to the EU accession of Poland, a possibility of financing a part of spending on human resources by the Structural Funds emerged. The paper shows the support of human resources in Poland in 2004-2006, implemented according to Narodowy Plan Rozwoju (National Development Plan). The article begins with a short description of the document's statements. It then shows the support of human resources in comparison with other expenses for the structural policy. The available results of implementing the support were also analyzed, with special attention paid to the regional divergence of it. An advantage of the capital region at the beginning of the implementation process, followed by a slight tendency to decrease, was pointed out. It is also stressed that an important part of the funds is going to be spent on fighting the unemployment, which shortened the sums engaged directly in building a knowledge based economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 428-437